(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: Experimental investigation of the vortioxetine effects on somatic and visceral nociception in mice. Material and method: We used healthy, non-genetically modified white Swiss mice (20-25 g), randomly assigned in 3 groups of 6 animals each, treated orally 14 consecutive days, as follows: Group I (DW): distilled water 0,1 ml/10 g body weight, Group 2 (VRT): 20 mg/kbw vortioxetine. In the 14th day of the experiment the Group 3 (KET) received the positive control drug ketoprofen (15 mg/kbw), 15 minutes before the performing the tests. The somatic pain testing was performed using hot plate assay. The writhing test based on chemical peritoneal irritation induced by diluted acetic acid (0,6%) was used as standardized visceral pain model. The data were statistically analyzed using SPSS variant 17.0 for Windows and ANOVA one-way method. The research protocol was approved by the Grigore T. Popa University`s Committee for Research and Ethical Issues. Results: Ketoprofen showed a substantial and progressive prolongation in reaction time in hot plate test, respectively a decrease in the behavioral manifestations in writhing test. The administration of vortioxetine resulted in a considerable increase in the time response to thermal noxious paws stimulation in hot plate test, and a diminution in the number of writhes in writhing test. Conclusion: Using the mouse models of acute pain hot plate analgesia meter and acid acetic writhing test, we revealed that the oral administration of vortioxetine during 14 days resulted in significant somatic and visceral analgesic effects, but less intense than of ketoprofen.